Feasibility Study of Small-sized FBAR-based Bandpass Filter Covering Digital Dividend Band for LTE Services - Yim, Munhyuk; Jeon, Buil; Yoon, Giwan (Journal of semiconductor technology and science, 2020)
In this paper, we present a feasibility study of a small-sized film bulk acoustic wave resonator (FBAR) bandpass filter (BPF) that covers the digital dividend band (698-862 MHz) for Long Term Evolution (LTE) services. The FBAR-based bandpass filter of 590×340 m2 is much smaller than the conventional filters of cavity, interdigital or discrete component configurations. This feasibility study will be very useful for realizing even more advanced LTE BPFs for wideband communications applications below 1 GHz. KCI Citation Count: 3